Chinese Finance under the Republic - Winston, A. P. (Quarterly Journal of Economics, 1916)
Introduction, 738. — I. Foreign loans to China, 740. — The international "money trust" described, 741. — Effect on interests of borrowers and lenders, 747. — Breakdown under pressure of competition, 749. — Critical comparison of the Taft and Wilson policies, 758. — II. Internal development of Chinese finance since the Revolution. The escape from bankruptcy, 1912–14, 762. — Political basis of the Chinese financial system, 765. — Influences tending toward improvement, 766. — The political and fiscal reorganization, 767. — First loans from Chinese lenders, 768. — Reform of salt administration, 771. — Fiscal economy, 774. — Political changes underlying these reforms, 775. — Summary of conclusions, 1912–16, 777.